Penerapan Restorative Justice Sebagai Implementasi Dari Ultimum Remedium Dalam Upaya Pengembalian Kerugian Keuangan Negara - Malik Ohoiwer; Abdul Manan; Mohamad Ismed (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
One of the basic objectives of eradicating corruption in Indonesia is to restore state losses. However, the retributive justice paradigm which is the legal basis for eradicating corruption and criminalizing corruption is not relevant to the main objective of corruption eradication law in Indonesia. What is even more important in the spirit of eradicating corruption, namely the return of state losses, is only an additional crime that can also be replaced by imprisonment. This article is intended to examine the concept of punishment for perpetrators of corruption that is relevant to be applied in Indonesia in accordance with what is required by law by considering the current development of the nation and state. The study focuses on deepening the elaboration of the concept of restorative justice to maximize the return of state finances in convicting perpetrators of corruption in Indonesia. By using normative juridical research methods, this study concludes that the concept of restorative justice in punishing perpetrators of criminal acts of corruption can be implemented in the form of strengthening norms for returning state losses from being an additional crime to being a principal crime. As for anticipating the perpetrators being unable to pay the losses, the concept of forced labour can be applied instead of imprisoning the perpetrators of corruption.Keywords: Restorative Justice; Ultimum Remedium; State Finance; Legal Benefits; SentencingAbstrakSalah satu tujuan dasar dari pemberantasan tindak pidana korupsi di Indonesia adalah untuk mengembalikan kerugian negara. Namun paradigma retributif justice yang menjadi landasan hukum pemberantasan tindak pidana korupsi serta pemidanaan pelaku korupsi tidak relevan dengan tujuan utama hukum pemberantasan korupsi di Indonesia. Hal yang justru penting dalam semangat pemberantasan korupsi yakni pengembalian kerugian negara justru hanya menjadi pidana tambahan yang juga dapat diganti oleh pidana penjara. Artikel ini dimaksudkan untuk meneliti konsep pemidanaan pelaku tindak pidana korupsi yang relevan untuk diterapkan di Indonesia sesuai dengan yang dikehendaki oleh undang-undang dengan mempertimbangkan perkembangan kehidupan bangsa dan negara dewasa ini. Kajian terfokus pada pendalaman mengelaborasi konsep restoratif justice untuk memaksimalkan pengembalian keuangan negara dalam pemidanaan pelaku korupsi di Indonesia. Dengan menggunakan metode penelitian yuridis normatif, kajian ini menyimpulkan bahwa konsep restoratif justice dalam pemidanaan pelaku tindak pidana korupsi dapat diimplementasikan dalam bentuk penguatan norma-norma pengembalian kerugian negara dari sebagai pidana tambahan menjadi pidana pokok. Adapun untuk mengantisipasi pelaku tidak mampu membayar kerugian tersebut, maka konsep kerja paksa dapat terapkan ketimbang memenjarakan pelaku tindak pidana korupsi.Kata Kunci: Restoratif Justice; Ultimum Remedium; Keuangan Negara; Kemanfaatan Hukum; Pemidanaan